Synthesis and Characterization of Some New Benzodiazepinium Salt Derivatives under microwave Irradiation - Baghdad Science Journal (مجلة بغداد للعلوم)
An attempt to synthesize the benzoimidazol derivatives from the reaction of o-phenylenediamine and benzoic acid derivatives in the presence of ethanol and various ketones under microwave irradiation, 1 , 5 - benzodiazepinum salt derivatives were obtained instead of them. Unexpected reaction was happened for synthesis a new series of benzodiazepinium salt derivatives in a selective yield . The reaction mechanism was also discussed. The new compounds were purified and identified their structures were elucidated using various physical techniques like; FT- IR spectra, micro elemental analysis (C.H.N) and 1H NMR spectra.